Result of Six Local Upland Rice Cultivars of East Kalimantan at Different Plant Spacing - R. Rusdiansyah; Yazid Ismi Intara; Budi Indra Setiawan (Chemical Engineering Diponegoro University, 2013)
The objective of this research was to evaluate the response of six upland rice cultivars from East Kalimantan over different plant spacing. The experiment was conducted at Kutai Kartanegara district in East Kalimantan, Indonesia. The experimental design used was the factorial experiment in Randomized Completely Block Design (RCDB) with three replications. The first factor was six upland rice cultivars of East Kalimantan, i.e.: v1 (Mayas Pancing), v2 (Gedagai), v3 (Bogor Putih), v4 (Mayas Putih), v5 (Serai) and v6 (Kunyit). The second factor was plant spacing i.e.: j1 (20 x 20 cm) and j2 (30 x 30 cm). The results showed that among the six cultivars, Gedagai, Bogor Putih and Kunyit produced higher yield than other varieties. Gedagai and Bogor Putih cultivars produced higher yield of 2.99 ton ha-1 at plant spacing 20 x 20 cm, whereas Kunyit produced higher yield of 2.66 ton ha-1 at plant spacing 30 x 30 cm. The agronomic characters showed that plant height of the six cultivars differed significantly at harvest time. In addition, highly significant differences of harvest time were observed of the six cultivars.Doi: http://dx.doi.org/10.12777/ijse.4.2.2013.66-68